Associations between smartphone addiction, parenting styles, and mental well-being among adolescents aged 15-19 years in Gujarat, India - M. Yogesh; Hemangi Ladani; Dipesh Parmar (BMC, 2024)
Abstract Background The pervasive use of smartphones among adolescents has raised concerns about addiction and its impact on mental well-being. This study investigates the prevalence of smartphone addiction and its associations with socio-demographic factors, parenting styles, and mental health among Indian adolescents. Methods A cross-sectional study was conducted among 560 school-going adolescents (aged 15-19) in Gujarat, India, from January to October 2023. Data was collected using validated scales: the Smartphone Addiction Scale-Short Version (SAS-SV), the Parenting Styles and Dimensions Questionnaire (PSDQ), and the Depression Anxiety Stress Scale-21 (DASS-21). Bivariate and multivariate logistic regression analyses were performed to identify factors associated with smartphone addiction. Results The prevalence of smartphone addiction was 64.6%. Urban residence (AOR: 2.4, 95% CI: 1.8-3.3), higher parental education (AOR: 3.3, 95% CI: 1.7-4.3 for graduate fathers), longer smartphone use (AOR: 2.08, 95% CI: 1.7-3.6 for > 3 years), and higher socioeconomic status (AOR: 1.9, 95% CI: 1.5-3.51) were associated with increased odds of addiction. Authoritarian and permissive parenting styles in both parents were positively associated with smartphone addiction, while authoritative parenting was negatively associated. Smartphone addiction was strongly associated with mental health issues, particularly with severe stress (AOR: 10.82, 95% CI: 5.11-22.88, p < 0.001). Conclusion Smartphone addiction is highly prevalent among Indian adolescents and is significantly associated with urban living, higher socioeconomic status, non-authoritative parenting styles, and poor mental health. These findings underscore the need for digital literacy programs, parenting interventions promoting authoritative styles, and mental health support to foster healthy smartphone use among adolescents.